Analysis of the profits cultivation of milkfish (Chanos chanos Forsskal) with different feeding at Pokdakan Simaranang, Ampekale village, Bontoa District, Maros Regency - Daris, Lukman; Masriah, Andi; Massiseng, Andi Nur Apung; Febri, Febri (Agrikan Jurnal Agribisnis Perikanan, 2021)
The purpose of this study was to analyze the level of profit for milkfish cultivators who used different feeds, namely cultivators who used feeds of (1) expired noodles or bread; (2) commercial feed; and (3) mixed feed between expired noodles or bread + commercial feed. The data obtained in this study were analyzed using variance (ANOVA) analysis to see the effect of different feeding on the profits of milkfish cultivators in the Simaranang fish cultivator group (Pokdakan), then continued with the W-Tuckey test to see the difference in profits between each cultivator. Based on the results of the analysis, it was found that the highest annual cultivation profit was obtained by cultivators who used a mixture of commercial feed and expired noodle/bread feed (Rp. 16,681,750/year) followed by cultivators who used commercial feed (Rp 9,123,000/year) and the profit. The lowest was experienced by cultivators who only used expired noodles/bread (Rp. 7,875,000/year).